Kajian Pemberian Makan Dan Minum Dalam Persalinan Ditinjau Berdasarkan Filosofi Kebidanan - Ni Wayan Suarniti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
The maternal mortality rate in Indonesia is still high, and the main cause is bleeding. One of the keys in prevention is Normal Childbirth Care with a compassion care approach to the mother, the first stage of care to provide food and drink to the maternity mother and refers to the philosophy of midwifery. Until now there are still a number of hospital practices in Indonesia, London and Canada restricting and even prohibiting pregnant women from eating and drinking if they are in labor due to safety concerns. This continues even though it has been disputed by the results of research that says that eating and drinking are very important as energy contributors during childbirth. The purpose of writing this article is to analyze the provision of food and drink in labor in terms of the philosophy of normal and natural child birth, woman care center and partnership, empowering woman. The result is that restrictions on eating and drinking in labor are futile and are not proven to provide safety and safety for maternity mothers. Eating and drinking are still needed to provide energy and prevent dehydration during childbirth, because a woman's body will be able to work if it has received physical and psychological nutrition. Conclusion: If the intake of nutrition and drinks is sufficient then the natural processes in the body, a woman's self-confidence will arise and she will be able to take responsibility for all the decisions that she goes through.